Sequential Production Planning Over Time at Minimum Cost - Johnson, S. M. (Management Science, 1957)
Production of a given commodity is to be scheduled over time to meet known future requirements while minimizing total costs. The costs include both storage and production costs as functions of time. The unit production cost is an increasing function of the production rate. Previous solutions to this problem have involved complicated iterative procedures. A new approach brings out the basic principle involved and leads to a surprisingly simple solution. This coincides with a common-sense technique sometimes used in business.